COMPARATIVE-LINGUISTIC ANALYSIS OF ROAD SIGN TERMINOLOGY IN ENGLISH AND UZBEK - Khushbaqova Nasiba Nurqobil qizi (Modern American Journals, 2026)
This article presents a comparative analysis of the semantic, structural, and pragmatic characteristics of road traffic terminology in English and Uzbek. The study reveals that English terminology tends toward a geometric and descriptive nature, whereas the Uzbek language prioritizes functional and prescriptive approaches. The findings highlight the phenomena of linguistic economy and explication within the language systems as exemplified by road signs.
Keywords: Cognitive linguistics, road signs, terminology, linguistic economy, explication, pragmatics, English, Uzbek.